CFD analysis of flow field and hydrodynamic compensation of poppet valve. Issue 1 (1st June 2022) - Li, Ruichuan; Liu, Jilu; Ding, Xinkai; Cheng, Yi; Liu, Qi
Abstract: The steady-state hydrodynamic force of cartridge valve poppet valve core reduces the stability of cartridge valve. A circular arc structure is added to the main valve core of the poppet valve to compensate the steady-state flow force. Referring to the structure and parameters of the actual cartridge poppet valve, the three-dimensional geometric model of the flow channel in the valve is established with UG software. CFD method is used to calculate and analyze the flow state of fluid in the poppet valve under the working state of the valve core, and the influence of the arc size and position of the valve core on the steady-state hydrodynamic compensation of the main valve core is studied. The results show that the circular arc structure can realize the hydrodynamic compensation of the valve core and increase the stability of the valve core. When the opening amount is small, properly increasing the height h of the circular arc structure can increase the static hydrodynamic compensation of the valve core; Keep the circular arc structure size L less than 1mm, and the static hydrodynamic compensation effect of the valve core is better.